Political clientelism and inequality in employment opportunities - García Godos Peñaloza, Luz Matilde (2023)
The study approaches the knowledge and identifcation of political clientelism and its consequences on inequalities inemployment opportunities in Latin America, within the framework of corruption in public administration. Our objective was to identify the characteristics of the formation of political clientelism that generate inequality in employment opportunities within the framework of political corruption. For the  methodology, being a review study, we considered the metadata narrative taking into account databases such as Scopus, with 16 articles; Web of Science, with 6 articles, and Scielo, with 9 articles. The exclusion criteria were: being outside the Latin American orb, political clientelism in the framework of elections, temporality greater than the search. The following keywords were used: clientelism corruption, labor inequality and public administration. The search was conducted in English, Portuguese and Spanish. The bibliographic manager Mendeley was used for references and information management. As a result, it was found that there is a structural clientelism, which has been formed according to the needs of governments, whose basis issystemic corruption. This leads to job opportunities that respond to political needs and not meritocratic ones.